2005
DOI: 10.1007/s10067-005-1084-y
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic portal hypertension associated with systemic sclerosis and Sjögren’s syndrome

Abstract: We report a patient with idiopathic portal hypertension (IPH) associated with systemic sclerosis (SSc) and Sjögren's syndrome. A 72-year-old Japanese woman was admitted to our hospital because of Raynaud's phenomenon, sclerodactyly, and dyspnea. The patient had splenomegaly, esophageal varices in the absence of extrahepatic portal obstruction, and cirrhosis of the liver. Immunological studies revealed positive anti-nuclear antibodies and high titers of anti-Scl-70, anti-SS-A, anti-centromere, and anti-mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Multiple studies have reported an association between INCPH/ PSVD and disorders of immune function including congenital [85] (in particular common variable immunodeficiency (CVID)) and acquired immunodeficiencies (human immunodeficiency virus (HIV)-related) as well as autoimmune diseases [2,10]. For example, INCPH has been described in patients with inflammatory bowel diseases, rheumatoid arthritis, systemic lupus erythematosus, autoimmune hepatitis, scleroderma, Felty's syndrome and celiac disease among others [10,24,28,29,40,[63][64][65]86]. Seropositivity for antinuclear, antimicrosomal and anti-DNA antibodies has also been reported [3,23].…”
Section: Immune Dysregulationmentioning
confidence: 99%
“…Multiple studies have reported an association between INCPH/ PSVD and disorders of immune function including congenital [85] (in particular common variable immunodeficiency (CVID)) and acquired immunodeficiencies (human immunodeficiency virus (HIV)-related) as well as autoimmune diseases [2,10]. For example, INCPH has been described in patients with inflammatory bowel diseases, rheumatoid arthritis, systemic lupus erythematosus, autoimmune hepatitis, scleroderma, Felty's syndrome and celiac disease among others [10,24,28,29,40,[63][64][65]86]. Seropositivity for antinuclear, antimicrosomal and anti-DNA antibodies has also been reported [3,23].…”
Section: Immune Dysregulationmentioning
confidence: 99%
“…Higher prevalence of INCPH in lower socioeconomic groups and experimental animal studies indicate an infectious etiology [ 3 , 52 , 58 , 59 ]. Especially in the West, INCPH is increasingly recognized in human immunodeficiency virus (HIV) patients [ 3 , 32 ].…”
Section: Etiologymentioning
confidence: 99%
“…[7][8][9][10] The etiology of IPH is still not clear. Some of the proposed etiological factors have included immunologic disorders, [11][12][13][14][15][16] chronic infection with some bacteria or human immunodeficiency virus, 13,[17][18][19] medication and toxins, [20][21][22][23][24] gene mutation, [25][26][27][28][29] and some other etiologies like dialysis. 30 The main clinical symptoms of IPH are those caused by portal hypertension, including splenomegaly, hypersplenism, hepatomegaly, gastrointestinal bleeding, ascites, and portal vein thrombosis (PVT).…”
Section: Introductionmentioning
confidence: 99%